Review of the Fund's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper ;, 2010)
This paper reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations. Since the last review, total arrears to the Fund declined by SDR 17.5 million to SDR 1,309.5 million. Payments to the Fund by Sudan and Zimbabwe were in excess of new obligations falling due, and a decrease in Somalia's arrears resulted from the full settlement of its overdue obligations to the SDR Department in the context of the general SDR allocation in August 2009.